Noble-metal-free p-n heterojunction of iron(III) hydroxide and graphitic carbon nitride for hydrogen evolution reaction. Issue 24 (15th December 2021) - Chen, Hongmei; Fan, Yanyun; Fan, Zheng; Xu, Hongyan; Cui, Danfeng; Xue, Chenyang; Zhang, Wendong
Abstract: Realizing efficient photocatalytic hydrogen production of graphitic carbon nitride (g-C3 N4 ) in the absence of precious metals is one of the urgent research topics for industrial application. In this work, efficient p-n heterojunction of iron(III) hydroxide and graphitic carbon nitride (Fe(OH)3 /g-C3 N4 ) for hydrogen production were successfully constructed using the electrostatic attraction self-assembly method. The Fe(OH)3 /g-C3 N4 heterojunction could harvest more visible light, suppress recombination and boost transmission rate of the carriers. As expected, without participation of any precious metal, the highest hydrogen production rate (733 μmol h −1  g −1 ) was 51.2 folds higher than the unmodified g-C3 N4 at λ > 400 nm, which is superior to many previous results. Additionally, a possible reaction mechanism was proposed according to energy band analysis as well as the experimental photocatalytic activity results. To the energy and environmental studies fields, this work suggests a novel approach to design high efficiency photocatalysts using abundant and inexpensive metals instead of precious metals.